THE COMPATIBILITY OF READING QUESTIONS IN THE ENGLISH COURSEBOOK FOR GRADE 8 WITH THE LEVEL OF THINKING SKILLS - Niswatul Mustafidah (Widya Mandala Surabaya Catholic University, 2018)
Coursebook is an effective media which contains instructions to enhance teaching and learning activities. There are several reasons proposed by Robert O’Neill (O'Neill, 1982) in using the coursebook. However, the educators especially teachers have to be clever in choosing a good coursebook. Some experts have certain criteria in choosing a good coursebook, but mostly they refer to the curriculum. Curriculum is the guideline of the national education. Nowadays, Indonesia uses a new curriculum called K-13 which stands for Curriculum 2013. Moreover, the government has published a coursebook entitled “When English Rings a Bell”. In the document of K-13, there is a competence achievement that should be achieved by the students in every level. The competence achievement refers to Revised Bloom Taxonomy (RBT) and the level of thinking skills which was proposed by Bloom. There are six levels in the level of thinking skills, which are remembering, understanding, applying, analyzing, evaluating and creating. According to the Curriculum 2013 – or K-13, the cognitive level that must be achieved by junior high school is in the domain of analyzing. This research would like to employ a checklist to analyze the reading questions in the coursebook. It is a valuable instrument to determine the cognitive level of the questions. In order to strengthen the data and make it valid, the researcher also applied data triangulation. The present study will analyze the compatibility of reading questions in the English coursebook grade 8 with the level of thinking skill.